Basics of Clinical Nutrition - Joshi YK; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2008)
The purpose of this book is to provide a workable knowledge of nutrition support and emphasize its importance in patient care. It is expected that the book will be useful to undergraduate medical and nursing students and also to the physicians. The effort has been made to cover most of the practical aspects of need and provision of nutritional support and also nutritional therapy in some of the common systemic diseases, where nutrition support is of importance in reducing mortality and morbidity leading to early recovery. Four new chapters viz. Nutritional assessment in clinical practice, Immunonutrition, Antioxidants and Probiotics have been added in this edition. The chapters have been written by a distinguished group of physicians, surgeons and dieticians who are actively practicing the nutrition support and also involved in research in this field. I am grateful to all the authors for their valuable contribution. The most important aim of this book is to help patients. It is hoped that the book will stimulate physicians, dieticians and nurses to put it into practice.
Keywords: Nutrition and Dietetics; Electronic books